Evolution of the Muslim judicial system - Kayadibi, Saim (Islamic Book Trust, 2011)
In the Islamic legal tradition, the judiciary has always played an important role in a state’s relationship with its citizens. The qadi (jurist) and the mahkamah (court) are well-known concepts. Their essential requirements, however, by means of which judicial development and practical considerations are essentially made, are less obviously identified. By undertaking detailed research on their roles in Muslim states, I show how social, cultural, political, and historical elements have shaped both of their roles in secular and non-secular environments. In the modern period, most Muslim-majority countries steadily adopted western legal systems and institutions due to the economic and political influence of their colonial masters. Out of this borrowing emerged a dual court system consisting of Shari‘ah courts as well as western-style secular and national courts. This paper analyzes the evolution of the judiciary and its institutions within Muslim states, including the function of dual court systems, with regard to the influence of social, cultural, and political elements.